Peran ayah terhadap perkembangan anak - Nisa, Layli Wahidati Aminun (Maliki Interdisciplinary Journal, 2023)
Children are individuals who grow and develop. They have physical, emotional and social needs that need to be met to support optimal growth and development. Children are generally considered to have great curiosity, quick learning abilities, and the potential to develop unique skills and personalities. In its development, the role of parents is needed, especially the role of a father. The role of fathers in child development is very important and varied. Fathers have a significant impact on the physical, emotional, and social aspects of children. The presence of a father can help in forming a child's self-identity, developing social skills, as well as assisting in the child's self-confidence and growing self-confidence. Father's involvement in daily activities, open communication, and emotional support can form a strong father-child relationship. Studies show that children who have a positive attachment to their father tend to have higher self-confidence and better social relationships. Therefore, the active participation of fathers in the lives of their children is very important to ensure balanced and optimal development.